Islam dan Gerakan Sosial: Studi atas Resistensi Guru Tarekat Menghadapi Pemerintah Hindia Belanda di Jawa Timur pada Akhir Abad XIX-Awal Abad XX - Wahyudhi, Johan (Jurnal Sejarah Indonesia, 2024)
This article proves several findings related to the crisis period involving the lives of teachers and religious practitioners in Java from the 19th to early 20th centuries. Even though their perspective on life is usually not concerned with world affairs, it is known that several Tariqa or Sufi teachers led social movements against the Dutch East Indies government. Of course, this was an anomaly, considering that usually the Company's enemies or people who the Company suspected from among Muslim religious leaders were kiai or hajjis. Tariqa teachers have a different identity from the two. Through social history research, by looking back at several records and reports left by the Dutch East Indies government, new information can be obtained about the involvement of this esoteric group in the arena of resistance against colonialists. Using historical research methods, several findings were obtained regarding the role of tariqa teachers in that period, especially in their efforts to build anti-colonial networks in East Java.